Darsan (to See) Lord Shiva in Varanasi. Visual Processes and the Representation of God by Seven Ricksha-Drivers - Wikström, Owe (Scripta Instituti Donneriani Aboensis, 1996)
In spite of its effort to be transculturally relevant, the psychology of religion is quite ethno- or rather Western-centric. This becomes very clear when one tries to "translate" Indian folk religiosity into concepts taken from mainline theories; i.e. social, cognitive or psychoanalytical psychology of religion. Not only do the norms and values differ, but the very ontological assumptions underlying the categories in which the researcher understand differs fundamentally from the internal Hindu anthropological and epistemiological apriori. For example, their words of the psyche include contextuality, from time to space, to ethics to groups. The subtle interrelatedness of the divine, spiritual and the mundane is obvious It includes the flows and exchanges of substances within and between persons with minimal outer boundaries. The author discusses the role of the visual and behavioural dimensions of the Indian religiosity.